Transcranial resection of the frontal and superior ethmoid sinuses - Palma, Eduardo; Rodríguez Martínez, Ricardo J; Arias, José; Pérez Lagrave, Alfredo; Pica, César; Palma, Liliana (Cirugía del Uruguay, 1976)
This paper describes a technique for transcranial approach and resection of frontal sinus, employed in 21 cases, over a period of 5 years with excellent results, no operatory deaths or complications. It has considerable advantages: it is simple and easy to perform; approach is sufficiently wide to permit total resection of multiple sinus recesses, lateral, supraorbital and posterior; there is resection of the deep bony wall of the sinus, which, combined with the re-expansion of the dura mater, totally eliminates the bony cavity of frontal sinus. and eliminates the possibility of formation of residual mucous recesses, while at the same time supressing the deep bony wall which is potentially pathological. It leaves no visible scars or bony depression and is, consequently aesthetically correct.